Construção de uma matriz de referência para o estudo das representações sociais sobre o desamparo docente - Carvalho, Lidiany Nunes de (2020)
This research paper aims to investigate the abandonment of the teachers based on the theoretical and methodological perspective of Moscovici’s Social Representation Theory (1961). This investigation has been proven to be currently relevant once it enlightens the subjective elements that compound our faculties. We started our research paper contextualizing the public school in the contemporaneity, focusing on the international policies that sometimes limit which kind of education will be offered to the working class in under-developed countries (LIBÂNEO, 2012; OLIVEIRA, 2004). We tried to emphasize how such policies, together with the normative speech of the “super-teacher” (FORMOSINHO, 2009), contribute to the abandonment of the professionals who face the classroom every single day. After, we showed the contributions of the Social Representation Theory (MOSCOVICI, 1961) for the exposure and understanding of the subjectivity of our faculties (ALVES-MAZOTTI, 1994; Villas BÔAS e SOUSA, 2011). The methodological trajectory has begun with the analysis, in social representation (MARKOVÁ, 2006) of the antonyms support and abandonment in popular dictionaries, following the methodology proposed by Lahou (2003). The data collected were processed through the software IRAMUTEQ, version R – 3.1.2. and revealed that the social representations of abandonment in dictionaries relate to the Freudian psychology. Then, we resorted to the Brazilian Digital Library of Dissertation and Thesis (BTDT, in Portuguese) to inventory co-related research that could be associated with the thematic of the abandonment. The analysis of these works culminated in the division of the abandonment of the teachers in four main aspects: professional qualification; work conditions; public policies; and psychosocial features. This way we elaborated a blueprint with five items for each of the main aspects mentioned. Due to the short length of the Professional MA course, our research paper might be evaluated, in future studies, by a “prestige” group (Stake apud Lima 2007) for the elaboration of its final version and to be applied to the teachers at some Brazilian public schools